Pedagogía sistémica como alternativa de cambio en educación básica. Un estudio de caso : Systemic pedagogy as an alternative for change in basic education. A case study - González de Pirela, Nelia; Zabala de Torres, Carmen; Miranda, Washington Rafael (Encuentro Educacional, 2024)
In order to write about systemic pedagogy, it is essential to consider education and family dynamics, because members of the family system are key actors in academic performance. This documentary study aimed to analyze the theoretical foundations of the orders of love of Hellinger (2001), Olvera (2016) and Pérez (2022), in order to recommend as a proposal guideline for improvements in student performance at school. The principles of systemic pedagogy and the strategies to address learning according to the characteristics of student performance at the Peniel Educational Unit were described, San Francisco, Zulia, Venezuela. The methodology focused on the case study method, with a qualitative approach, bibliographic and descriptive review techniques were used with the matrix analysis instrument to tabulate the theoretical - practical data applied to the school under study. As a result of the research, teacher training guidelines were constructed, focusing on systemic pedagogy with the participation of the family and the integration of academic areas in the design and development of the classroom pedagogical project to contribute to the improvement of academic performance, with the development of an action plan to improve student performance. It was concluded that the practice of the orders of love, the application of systemic strategies plus the participation and integration of the entities involved in the school contribute to the improvement of student performance.